PERANAN PELAYANAN ADMINISTRASI DALAM MENINGKATKAN PARTISIPASI MASYARAKAT PADA KANTOR LURAH SIRONGO FOLARAHA KECAMATAN TIDORE UTARA KOTA TIDORE KEPULAUAN - Ilfan Baharuddin (Yayasan Akrab Pekanbaru, 2019)
This study aims to determine the impact or influence of administration on community participation in development and development in Sirongo Folaraha Subdistrict North Tidore Subdistrict, Tidore Islands City, with the formulation of the problem